Modal sosial pengembangan usaha budidaya tambak di Desa Towua Kecamatan Wundulako Kabupaten Kolaka - Rahmadani, Zaenab; Hamzah, Awaluddin; Rosmawati (Jurnal Sosial Ekonomi Perikanan, 2021)
The study was conducted in Towua Village, Wundulako District, Kolaka Regency during the period from February to April 2019, in order to find out the social capital that occur intertwined between farmers. Respondents in this study were 20 farmers who were obtained through random sampling. Data collection through direct interviews using questionnaires. The research variables measured and observed were networks, collaboration, beliefs, social norms, citizenship and proactive actions. The result of this study showed, there are 5 (five) elements of social capital that occur intertwined between farmers namely network, collaboration, belief, social norms and citizenship. In the network element, occurs in the process of buying and selling and information on aquaculture as well as assistance from the Marine and Fisheries Office of Kolaka Regency; Cooperation. in the form of mutual assistance between farmers; Trust, in lending money between farmers without conditions; The social norms, agreed by the farmers are obliged if there are activities to clean the waterways around the ponds and Citizenship as good cultivators, they always give their voting rights every election. Network as a place to get information, cooperation forms familiarity between farmers; Trust will arise when a bond in a group the higher the possibility of establishing cooperation and will run for a long time; Social norms are informal norms that have existed for generations that were still adhered by the community; and Citizenship is an acknowledgment given to farmers in the form of recognition of the right to vote in the community. The elements of social capital are a foundation for achieving a goal or for maintaining business continuity.